Synthesis and characterization of nanocrystalline hydroxyapatite from natural bovine bone - A. Ruksudjarit (2018)
Nanocrystalline hydroxyapatite (HA) powder was synthesized from natural bovine bone by a vibro-milling method. The bovine bone had been deproteinized by hot water before it was calcined at 800 °C for 3 h. The resulting product was crushed into small pieces and milled in a ball mill pot for 24 h. After that the powders were ground by the vibro-milling method with various milling times. Characteristics of the powders were then investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDS). Nanocrystalline HA powder with diameter less than 100 nm were revealed from the samples using vibro-milling time of 2 h, 4 h and 8 h. Ca/P molar ratio in the powder was 1.66 which is close to the theoretical value that found in the pure hydroxyapatite. © 2007 Elsevier B.V. All rights reserved.